Youth Camp for Preventing Violent-Extremism: Fostering Youth Dialogue, Encountering Diversity - Garadian, Endi Aulia (Studia Islamika, 2018)
On the Saturday late night, 10th February 2018, Basit––an Islamic teacher (ustādh)––admonished street children because of their perturbing behaviours in the front of his store. However, feeling offended by the ustādh, the children had battered down of him instead. His right hand was severely torn due to knife cuts and got a bruised face after being showered with punches from the children. On the next day, 11th February 2018, Mass (Divine Liturgy) at St. Lidwina Church in Sleman, Yogyakarta turned out to be “Bloody Mass” after being attacked by a 23-year-old young man. Allegedly running toward choir, the youngster swung repeatedly his blade in the front of the church and slashed pastor, churchgoer, church congregation and police officer as well.DOI: 10.15408/sdi.v25i2.7924